Transformasi Tata Kelola Arsip di Kantor Wali Nagari Dilam, Kec. Bukit Sundi, Kab. Solok - Erlianti, Gustina; Zuve, Farel Olva; Fudhla, Nora (Universitas Negeri Padang, 2022)
Rapid technological developments are not directly proportional to the management of records in an agency. This is evidenced by the fact that there are still many agencies that still manage their archives manually so that it takes a long time for the processing to reach the information retrieval process. One agency that has not yet managed its archives electronically is the Wali Nagari Dilam Office, Solok Regency. Therefore, there is a need for training related to managing records electronically using the ARTERI application to make it easier for village officials to manage their records. After conducting the training, there was an increase in the ability of the participants by as much as 70% so it is hoped that it will increase again so that all archives can be managed properly and can be found quickly and precisely.